Faktor-Faktor di Industri Galangan Kapal yang Dapat Berkontribusi pada Isu Perubahan Iklim - Taufik Hidayat (SPECTA Journal of Technology, 2017)
The shipbuilding industry is the fabrication industry in sectors involving the use of heavy equipment materials and manufacturing practices can have an impact on the environment and thus can contribute to climate change. This study reviewed the literature to use the approach can imagine a process that impact on the environment, and occurs in the shipbuilding industry. The hope can give the shipbuilding industry a chance to set a long-term vision on an individual basis, not because in the end was forced to make as a result of coercion by the government or the pressure of the surrounding community, but also address the environmental impact more effectively, and perhaps even get a commercial advantage from the innovations developed. This can be realized with the implementation of management strategies. Management strategy is a series of decisions and managerial actions that determine the long-term performance of the corporation. Where this includes environmental-scanning (external and internal), strategy formulation (planning long-term strategy), strategy implementation, and evaluation and control. So this study emphasizes the monitoring and evaluation of external opportunities and threats on the strengths andweaknesses of the corporation. The results of this study establish a six-facto-a major factor in the shipbuilding industry that can contribute to climate change, namely material handling, metal working, the noise, the government and the surrounding community, the level of technology, and ship recycling.